High Spin Magnetic Moments in All-3d-Metallic Co-Based Full Heusler Compounds - Tas, Murat; Ozdogan, Kemal; Sasioglu, Ersoy; Galanakis, Iosif (MDPI, 2023)
We conduct ab-initio electronic structure calculations to explore a novel category of magnetic Heusler compounds, comprising solely 3d transition metal atoms and characterized by high spin magnetic moments. Specifically, we focus on Co(2)YZ Heusler compounds, where Y and Z represent transition metal atoms such that the order of the valence is Co > Y > Z. We show that these compounds exhibit a distinctive region of very low density of minority-spin states at the Fermi level when crystallizing in the L2(1) lattice structure. The existence of this pseudogap leads most of the studied compounds to a Slater-Pauling-type behavior of their total spin magnetic moment. Co2FeMn is the compound that presents the largest total spin magnetic moment in the unit cell reaching a very large value of 9 mu(B). Our findings suggest that these compounds are exceptionally promising materials for applications in the realms of spintronics and magnetoelectronics.
Keywords: Heusler compounds; ab-initio calculations; first-principles; electronic structure; ferromagnetic materials; Slater-Pauling rule; BAND-STRUCTURE; ALLOYS; COMBINATORIAL; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics